Facing up : science and its cultural adversaries - Weinberg, Steven, 1933-2021 (Harvard University Press, 2003)
In a New York Times profile, James Glanz remarked, "Steven Weinberg is perhaps the world's most authoritative proponent of the idea that physics is hurtling toward a "final theory," a complete explanation of nature's particles and forces that will endure as the bedrock of all science forevermore. He is also a powerful writer of prose that can illuminate--and sting ... He recently received the Lewis Thomas Prize, awarded to the researcher who best embodies 'the scientist as poet.'" Both the brilliant scientist and the provocative writer are fully present in this book as Weinberg pursues his principal passions, theoretical physics and a deeper understanding of the culture, philosophy, history, and politics of science. Each of these essays, which span fifteen years, struggles in one way or another with the necessity of facing up to the discovery that the laws of nature are impersonal, with no hint of a special status for human beings. Defending the spirit of science against its cultural adversaries, these essays express a viewpoint that is reductionist, realist, and devoutly secular. Each is preceded by a new introduction that explains its provenance and, if necessary, brings it up to date